Music as a collaborating actor: new insights into the nature and role of music in psychedelic-assisted psychotherapy - Dwyer, Justin; Johnston, Robert B.; O’Callaghan, Clare; Kallianis, Voula; Ross, Margaret L. (Frontiers in Psychiatry, 2025)
BackgroundMusic has been identified as a central feature of psychedelic-assisted psychotherapy (PAP) and has hitherto been understood to amplify the psychedelic experience in a predictable way that has been codified into music recommendations and playlists.Purpose of studyTo re-evaluate the nature and role of music within the participant’s world during psychedelic-assisted psychotherapy.MethodPhenomenological analysis of participants’ descriptions of music during a randomised control trial of PAP at end of life involving two doses and a semi-structured interview following each dose.FindingsMusic undergoes a profound change during PAP that radically transforms it from everyday recorded music into a series of internally generated multisensory and deeply personal experiences that arrive fully formed and are instantly known by the participant. Some of these are constituted into actors that collaborate with the participant and the psychotherapist in their ongoing psychotherapy endeavours. This stands in stark contrast with the everyday properties of music described by those in the placebo group.ConclusionsAn alternate understanding of music in PAP is suggested that radically departs from the view that music is “administered” as part of PAP. There are profound implications for the practise of PAP and further research.Clinical trial registrationAustralian New Zealand Clinician Trials Registry identifier, ACTRN12619001225101.